Human resource management in virtual organizations - Heneman, Robert L.; Greenberger, David B. (Emerald Publishing Limited : Information Age Pub., 2002)
Sections covered in this book include: defining virtual organizations and implications for human resource management; outsourcing human resources; job analysis and competency assessment; training and development; performance management; compensation; and negotiations.
Keywords: Personnel management -- Technological innovations.; Virtual reality in management.; Business & Economics -- Human Resources & Personnel Management.; Personnel and human resources management.; elektronické knihy; electronic books